Pengaruh Keterlibatan Pemakai, Pelatihan dan Pendidikan, Formalisasi Pengembangan, dan Ukuran Perusahaan Terhadap Kinerja Sistem Informasi Akuntansi Pada Perusahaan Prudential di Kota Denpasar - I Putu Scyangga Dana; A.A.A Erna Trisna Dewi; I.B Made Putra Manuaba (Jurnal Riset Akuntansi Warmadewa, 2020)
Typically a system can be said to be successful if the system is able to meet three conditions, namely increased use of the system itself, user perceptions of the quality of the system are better than before, or increased user satisfaction of the system. This research was conducted at the Prudential Company in Denpasar, which is located at Jalan Hangtuah, Sanur Raya shopping center no. 1 Denpasar. The sampling technique used in this study was purposive sampling method, which is a sampling technique with certain considerations. The data collection method used in this research is a questionnaire method. The analysis technique used is the multiple linear regression analysis method. Based on the calculation results, there is a positive influence on the user involvement variable on the performance of the accounting information system, there is a positive influence on the training and education variables on the performance of the accounting information system. companies on the performance of accounting information systems.